2013
DOI: 10.1242/dev.086785
|View full text |Cite
|
Sign up to set email alerts
|

Notch cooperates with Lozenge/Runx to lock haemocytes into a differentiation programme

Abstract: SUMMARYThe diverse functions of Notch signalling imply that it must elicit context-specific programmes of gene expression. With the aim of investigating how Notch drives cells to differentiate, we have used a genome-wide approach to identify direct Notch targets in Drosophila haemocytes (blood cells), where Notch promotes crystal cell differentiation. Many of the identified Notch-regulated enhancers contain Runx and GATA motifs, and we demonstrate that binding of the Runx protein Lozenge (Lz) is required for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 84 publications
11
121
0
Order By: Relevance
“…Furthermore, the Friend of GATA transcription factor U-Shaped (Ush) acts in combination with a Srp splice variant (SrpNC) to inhibit the development of CCs (Fossett et al, 2003). Recently, Lz expression was shown to necessitate Notch activation of CC development, and this effect partially reflects Notch activation of the transcription factor Klumpfuss (Klu), another zinc-finger protein (Terriente-Felix et al, 2013). In comparison, the Pacifastacus transcriptome expressed several GATA factors, one of which was specifically similar to Srp.…”
Section: Proteins In P Leniusculus Hematopoiesis -A Comparison With mentioning
confidence: 99%
“…Furthermore, the Friend of GATA transcription factor U-Shaped (Ush) acts in combination with a Srp splice variant (SrpNC) to inhibit the development of CCs (Fossett et al, 2003). Recently, Lz expression was shown to necessitate Notch activation of CC development, and this effect partially reflects Notch activation of the transcription factor Klumpfuss (Klu), another zinc-finger protein (Terriente-Felix et al, 2013). In comparison, the Pacifastacus transcriptome expressed several GATA factors, one of which was specifically similar to Srp.…”
Section: Proteins In P Leniusculus Hematopoiesis -A Comparison With mentioning
confidence: 99%
“…Among 25 putative Notch-regulated genes encoding cellmorphogenesis-related proteins that were identified through genome-wide studies (Djiane et al, 2012;Krejci and Bray, 2007;Terriente-Felix et al, 2013), we found that 12 are essential for generating adult flies capable of flight, consistent with appropriate functions in muscle formation. Focusing on three, Reck, rhea/talin (hereafter referred to as talin) and trio, we demonstrate that they are expressed in adult muscle progenitors and exhibit Notch regulation.…”
Section: Introductionmentioning
confidence: 72%
“…The best characterized target genes of Notch encode transcription factors of the HES/E(spl) and Hey/Hesr/Herp gene families (Iso et al, 2003) but more-recent genome-wide studies have uncovered a broader spectrum of Notch-regulated genes (Djiane et al, 2012;Hurlbut et al, 2009;Krejcí et al, 2009;Mazzone et al, 2010;Terriente-Felix et al, 2013;Wang et al, 2011). Among these are genes directly involved in cell shape, cell organization and cell behaviour, whose functional relevance downstream of Notch has not been explored, despite the fact that Notch has been implicated in different morphogenetic processes independently of cell fate.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic NOTCH complexes are found mainly associated with enhancers or super-enhancers in different cell types [14•]. These sites are closely associated with RUNX1 binding sites, an association previously observed in Drosophila [15]. The biological meaning of Notch binding to the super-enhancers is as yet unknown, but it could have a role as an integrator of signaling pathways [16••].…”
Section: Nuclear Signaling and Chromatin Regulationmentioning
confidence: 99%